The Role of School Directors in the Effective Management of Secondary Schools - Grđan, Zdravka (Digital Repository of Theses - SSBM Geneva, 2025)
Effective management is a critical factor in ensuring the success of public secondary schools. The role of school directors is particularly significant, as they must navigate a complex array of challenges to align institutional goals with national educational priorities, ensure compliance with legal frameworks, and address the expectations of a diverse set of stakeholders. Consequently, understanding the role of school directors in public secondary education requires a comprehensive examination of management principles, contextual factors, and cross-sectoral insights. At its core, management in secondary schools involves the integration of planning, organizing, leading, and controlling to create environments that foster learning and development. However, these managerial functions cannot be understood in isolation, as they are deeply influenced by the external environment, including regulatory requirements, funding mechanisms, and community dynamics. In addition to navigating the regulatory environment, school directors must contend with the unique challenges posed by the public secondary education sector. Public schools serve a diverse student population, with varying needs and expectations that require tailored approaches to teaching and learning. Moreover, the public nature of these institutions means that directors are accountable not only to their immediate stakeholders, such as teachers and parents, but also to the broader community and government authorities. This accountability is further amplified by the increasing demand for transparency and efficiency in public sector management, which places additional pressure on school directors to demonstrate measurable outcomes in areas such as student performance, resource utilization, and stakeholder satisfaction. One of the most significant aspects of the director’s role in public secondary schools is their engagement with stakeholders. Stakeholder management in education is inherently complex, as it involves balancing the often-conflicting interests of different groups. For example, parents may prioritize the safety and well-being of their children, while teachers may focus on professional development and academic freedom. At the same time, government authorities are primarily concerned with compliance, efficiency, and alignment with national education policies. The director’s ability to navigate these diverse expectations is critical to the success of the school, as it fosters trust, collaboration, and a shared commitment to achieving institutional goals. The evolving role of school directors also reflects broader trends in educational leadership. Globally, there has been a shift toward more inclusive and participatory models of governance, where school leaders are expected to engage with their communities and involve stakeholders in decision-making processes. In Croatia, this trend is evident in initiatives that emphasize the importance of parental involvement, community partnerships, and teacher collaboration in shaping school policies and practices. These developments align with contemporary management theories, such as stakeholder capitalism, which emphasize the need to balance the interests of multiple constituencies to achieve sustainable outcomes. For school directors, adopting such an approach requires not only a deep understanding of management principles but also the interpersonal skills to build and sustain relationships across diverse stakeholder groups. To address these challenges, school directors must draw on a combination of theoretical knowledge and practical experience. Theoretical frameworks, such as Fayol’s principles of management and transformational leadership theories, provide valuable insights into the core functions of management and the characteristics of effective leadership. At the same time, practical experience enables directors to adapt these principles to the specific contexts and challenges of their schools. This interplay between theory and practice is particularly important in the public secondary education sector, where directors must balance the demands of day-to-day operations with the strategic goal of improving educational outcomes.